A study on the energetic electron precipitation observed by CSES. Issue 6 (10th December 2018) - Wang, YaLu; Zhang, XueMin; Shen, XuHui
Abstract : High energy particles are the main target of satellite space exploration; particle storm events are closely related to solar activity, cosmic ray distribution, and magnetic storms. The commonly seen energetic particle (electron) precipitation anomalies include mainly the inner and outer Van Allen radiation belts, the South Atlantic Anomaly, and the anomalous stripes excited by artificial electromagnetic waves. The China Seismo‐Electromagnetic Satellite (CSES), launched in February of 2018, provides a platform for studying ionospheric particle disturbances. This paper reports the first studies of electron precipitation phenomenon based on high energy particle data from the CSES. We find that the global distribution of electron fluxes in the low energy band (0.1–3 MeV) can relatively well reflect the anomalous precipitation belt, which is consistent with results based on the DEMETER satellite, indicating that the quality of the low‐energy band payload of the CSES is good. In addition, this paper makes an in‐depth study of the electron precipitation belt excited by the NWC artificial VLF electromagnetic transmitter located in Australia, which appears as a typical wisp structure on the energy spectrum. The magnetic shell parameter L corresponding to the precipitation belt ranges from 1.44 to 1.74, which is close to the L value (~1.45) of the NWC transmitter; the energy of the precipitation electrons is between 100 keV and 361.57 keV, among which the precipitation of 213.73 keV electrons is most conspicuous.